Brain Drain: Greece’s Open Wound - Tsertekidis, Georgios (HAPSc Policy Briefs Series, 2023)
The phenomenon of brain drain, which refers to the emigration of highly skilled individuals from their home country, has been a long-standing challenge for Greece. After the global financial crisis of 2007 – 2009 struck the country, scholars have observed the escalation of brain drain, the loss of valuable human capital in terms of social and economic growth and development. The current phenomenon is linked throughout the relevant literature with other eras of the Greek past. Of course, beyond the historicity of the phenomenon, there are new factors that affect the current status. This policy brief attempts to work with the existing knowledge on the subject and recommend some policy directions.